KINETIC MODEL FOR FISCHER-TROPSCH SYNTHESIS OVER NANOPARTICLES IRON CATALYSTS WITH POLYMER MATRIX IN A SLURRY REACTOR - A. H. Al-Khazraji; A. V. Krylov; M. V. Kulikova; V. R. Flid; O. Yu. Tkachenko (Тонкие химические технологии, 2016)
Influence of additives of synthetic polymers of various natures on reactionary ability of the nanostructured iron catalysts in the three-component Fe-paraffin-polymer system in Fischer-Tropsch (FTS) in the slurry reactor was studied. The polymers used: polyacrylonitrile (PAN), polyvinyl alcohol (PVA), polystyrene, cross-linked with divinylbenzene (PS-DVB), polyamide-6 (PA). The catalysts obtained by droplet thermolysis is influenced by, the nature of the stabilizing polymer. Besides the conversion of the synthesis gas depends on the contact time and is between 10 to 80%. The highest rate of FTS is observed in the Fe-paraffin-PAN. The conditions of synthesis in Fe-paraffin-polymer systems produced a wide range of saturated and unsaturated compounds. It is found that the nature of the stabilizing polymer also affects the olefin /paraffin ratio. Based on experimental data the analysis of kinetic models for the flow of CO is carried out, a kinetic and thermodynamic characteristics of the process was obtained. The relationship between the values of the activation energies and the nature of the stabilizer was established.